PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL DIBIDANG PATEN - Mastur Mastur (Qistie Jurnal Ilmu Hukum, 2012)
Intellectual  Property  Rights  are  rights  derived  from  the  work,  initiative  and creativity  in  the  form  of  a  real  man.  Intellectual  Property  rights  consist  of privately owned property and Industry. Patents are part of Intellectual Property Rights  in  Industry.  Patents  are  granted  the  right  of  the  government  and  is exclusive. Exclusive rights of patent holders is the production of a patented item,   usage  and sales  of goods and deeds relating  to  the  import and sale of such goods store.  Legal  protection  of  intellectual  property  rights  in  the  patent  field ketetentuan regulated in Law Number 14 of 2001. In chapter 8, paragraph   (1) time protection for 20 years from the date of receipt and can not be extended. And Article 9  set period of patent protection  for  simple  for 10  (ten) years and can not be extended. Protection of  intellectual property rights  is no guarantee  to  the public  to respect  the  right  of  initiative  and  the  reaction  and  to  provide  protection will upload their work. The higher appreciation of the intellectual property rights of a nation  then  the  future will be better .Keywords:  Intellectual Property Rights, Patent Protection